Coalescence of inter: Osteotomy bone graft material inserted via separate transcrestal sinus osteotomies: A case report and concise review of the literature - McCrea, Shane J. J. (European Journal of Dentistry, 2014)
When multiple implants are to be placed, and a pneumatized sinus exists, the published reports suggest that the lateral window approach (LWA) is favored for sinus floor augmentation. Simultaneously, if a transcrestal sinus floor augmentation has been carried out (bone-added osteotome sinus floor elevation), the reports are restricted to single implant placement at any site. The aim of this study was to evaluate the clinical and radiographic outcomes at adjacent transcrestal sinus augmentation grafts using deproteinized bovine bone material, with the immediate placement of submerged adjacent implants, and so determining the fate of the graft material. The progressive loss of the inter-implant graft is reported for the LWA Technique. However, this novel coalescence method has shown a progressive increase in the inter-implant graft region, thus inferring a positive bony regeneration and remodelling at the region. These results indicate that the carrying out of a large scale study is warranted to confirm the efficacy of this technique.
Keywords: Dental implants; sinus graft; transcrestal; xenograft